Proceedings of the Thirtieth International Joint Conference on Artificial Intelligence 2021
DOI: 10.24963/ijcai.2021/32
|View full text |Cite
|
Sign up to set email alerts
|

Fair and Efficient Resource Allocation with Partial Information

Abstract: We study the fundamental problem of allocating indivisible goods to agents with additive preferences. We consider eliciting from each agent only a ranking of her k most preferred goods instead of her full cardinal valuations. We characterize the amount of preference information that must be elicited in order to satisfy envy-freeness up to one good and approximate maximin share guarantee, two widely studied fairness notions. We also analyze the multiplicative loss in social welfare incurred due to the lack of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 1 publication
(9 reference statements)
0
9
0
Order By: Relevance
“…It is easy to see that α-balancedness implies α-proportionality. 2 Balancedness and similar cardinality constraints have been investigated previously in various fair division contexts (Leroux and Leroux 2004;Biswas and Barman 2018;Bei et al 2021b;Halpern and Shah 2021); in our case, note that 1-balancedness is equivalent to envy-freeness.…”
Section: Introductionmentioning
confidence: 53%
“…It is easy to see that α-balancedness implies α-proportionality. 2 Balancedness and similar cardinality constraints have been investigated previously in various fair division contexts (Leroux and Leroux 2004;Biswas and Barman 2018;Bei et al 2021b;Halpern and Shah 2021); in our case, note that 1-balancedness is equivalent to envy-freeness.…”
Section: Introductionmentioning
confidence: 53%
“…managed to close a gap on the price of EF1 that was le open in the work of Bei et al [2021], and also showed tight bounds for other fairness notions, in particular, 1/2-MMS and Prop1. Halpern and Shah [2021] showed tight bounds on the Price of EF1 and of approximate MMS under the constraint of having only ordinal information about the agent values, a typical assumption made in the context of distortion in social choice [Anshelevich et al, 2021].…”
Section: Fairness and Efficiencymentioning
confidence: 99%
“…Furthermore, showed tight bounds for other fairness notions, in particular, for 1/2-MMS and Prop1. Halpern and Shah [2021] showed tight bounds on the price of EF1 and of approximate MMS under the constraint of having only ordinal information about the agent values, a typical assumption made in the context of distortion in social choice [Anshelevich et al, 2021].…”
Section: Opt(i) Sw(a)mentioning
confidence: 99%
“…Let H n = Θ(ln n) be the n-th harmonic number. Halpern and Shah [2021] showed that with only ordinal information, it is impossible to achieve be er than 1/H n -MMS, while in previous work, Amanatidis et al [2016] showed that 1/2H n -MMS allocations can be computed. Hosseini et al [2021] showed the existence of Pareto optimal and MMS or EFX allocations when agents have lexicographic preferences.…”
Section: Limited Informationmentioning
confidence: 99%